Postharvest physiology of plantain and banana: IITA research guide, No 64 - Hartley, P. (1998)
Postharvest research is concerned with maintaining crop quality until the crop reaches the consumer. Postharvest physiology includes study of the physiological development of fruits, and their metabolic processes, especially transpiration and respiration. Postharvest improvements aim to slow down these processes, to extend storage life, and improve fruit quality.